Investigating the performance of an anaerobic baffled bioreactor for the biodegradation of alkaline-surfactant-polymer in oilfield water. Issue 20 (18th October 2018) - Liu, Changli; Zhang, Rongshu; Yang, Hongyi; Zhang, Jie; Wang, Hongwei; Chang, Le; Zhan, Yuanlong; Xu, Qijiang
ABSTRACT: The anaerobic baffled reactor (ABR) was used to treat alkaline-surfactant-polymer (ASP) flooding wastewater in the Daqing oilfield. With the ABR, hydraulic retention time (HRT)was reduced from 72 to 24 h, the bioreactor purification capability gradually improved. After the ABR running for 100 days, the removal rate of raw oil, suspended solid and surfactant reached 99.8%, 94.4% and 50%, respectively; alkali, polymer and viscosity were removed at a rate of about 16%, 7% and 20%, respectively. There were 39 kinds of organic materials detected by GCMS in the original water sample, while only 12 kinds of organics were left in the ABR outfall. The above results showed that the anaerobic, facultative anaerobic and aerobic compartment of ABR have strong capability of biodegrading petroleum pollution matter. Pyrosequencing analysis of the 16S rRNA indicated that Acinetobacter, Arcobacter, Pseudomonas and Paracoccus were the dominant bacteria genera present in the ABR reactor, among them Acinetobacter was the dominant species in the bacterial community.